Statement to the 47th Session of the United Nations General Assembly New York October 6 1992 - Turnquest, Orville A. (Ministry of Foreign Affairs, Bahamas NassauBS, 1992)
Identifies a number of critical issues which require urgent international attention viz. the situation in Haiti; problems caused by the drug trade and the delay of majority rule in South Africa. Attributes the success of the Earth Summit to the large measure of cooperation fostered by the UN and reiterates the Bahamas' commitment to the protection of its natural environment as well as promotion of the Global Environment. Expresses the view that the performance of the world economy can be improved through the enhancement of international cooperation and policy coordination which should be a principle objective of the UN.